Scada for Prototype of Multi Area Parking System Based on PLC M221 - Yudarmawan, Agustinus VD Bruin; Setiyani, Theresia Prima Ari (SENATIK STT Adisutjipto, 2019)
SCADA for the prototype M221 PLC-based multi-area car parking system is a system for managing several separate car parks on line via ethernet. The system is equipped with HMI as an interface to facilitate operators to monitor system conditions in real-time and the ability to display data on the number of vehicles entering and exiting, counting the number of vehicles parked for one day, and calculating revenue throughout the day. Loop sensor is used to detect vehicles that will enter or exit the parking door. Input from the sensor will be processed by the PLC to move the doorstop motor, indicator lights and update the display on the HMI. The results of a multi-area prototype test process for a car parking system for two parking areas have worked well. The system is able to control the opening and closing of the entrance and exit bars, controlling the indicator lights whether or not the parking area is full, showing the animation of the system process to the HMI in real time, calculating the number of vehicles and calculating the total cost of revenue in each parking area.